Nigerian national income accounts: historical summary and projections to 1985 - Cownie, John (Michigan Michigan State University, 1968)
Projections presented in this paper focus primarily on the differential growth effects attributable to alternative policies towrd export agriculture
osc 20/08/2021
Arch
Keywords: National income; Nigeria